INTERACTION BETWEEN POND-BOTTOM SOIL AND WATER QUALITIES - Mollah, M F A; Haque, A K M Aminul; Eaqub, M; Idris, M; Chaudhury, M Y (Indian Journal of Fisheries, 2011)
Considerable monthly variations were observed in soil properties and water qualities of two ponds during a six-mo:ith period. The textural class of soil of .Pond 1 was silt loam and that of Pond 2, in general, silty day loam. The in-wash of silt, etc., with the large volume of surface run-off of rain water from the surrounding agriculture farm, and the suspension of the dead self-vegetation of the pond, resulted in the lowest value of transparency in Pond 1 being recorded during July; whereas, the relatively abundant growth of phyto-plankton in Pond 2 was responsible for reduced transparency there in May and again in August, as compared with the same in the remaining four months of the study period. The pH of bottom soil and of water indicated that Poivd 2 is more suitable for fish culture